Quantum tunnelling and charge accumulation in organic ferroelectric memory diodes - Matteo Ghittorelli (Nature Portfolio, 2017)
Organic non-volatile memories based on ferroelectric and semiconductor polymers are one of promising candidates for flexible electronics, yet the relevant device physics remains elusive. Ghittorelliet al. show that quantum tunnelling and charge accumulation govern the ferroelectric memory operation.